Upaya Pencegahan Kebisingan di Industri Petrokimia - Endrixs Endrianto (Journal on Education, 2023)
Workplace noise often becomes a problem for workers, but the noise experienced by petrochemical workers can cause physiological, psychological, communication, and balance disturbances. The purpose of this final project is to identify the sources of noise and efforts to prevent noise in the petrochemical industry. Noise is an unwanted sound from activities or operations over a period of time, and can certainly cause health problems for humans and environmental discomfort. The research method used in this final project is a qualitative method, which is used to investigate, discover, describe, and presented using descriptive methods. From the results obtained, it is known that the sources of noise are physiological disturbances, psychological disturbances, communication disturbances, and deafness. The efforts to prevent noise include technical prevention, administrative noise prevention, and the last resort of noise prevention. The conclusion of this final project is that for any job that involves noise, prevention efforts must be made by measuring the intensity and threshold limit value at the workplace to be 85 dB for 8 hours per day, and prevention efforts must be made using technical, administrative, and the last resort of noise prevention methods. It is recommended that workers who are exposed to noise must use appropriate personal protective equipment (PPE) for their work.